Il Telefono & Dintorni Una selezione di eventi, contributi ed «immagini» dalle celebrazioni per il bicentenario della nascita di Antonio Meucci - Angotti, Franco; Pelosi, Giuseppe (Proceedings e report, 2011)
Sponsored by the University of Florence, the "National Committee for the celebrations of the bicentenary of the birth of Antonio Meucci" had multiple goals. These included: fostering a knowledge of the historic period in which Antonio Meucci lived in Florence, where he was born on 13 April 1808; contributing to spread and enhance technical-scientific culture among secondary school and university students; offering an occasion for reflection on the future of telecommunications from the perspective of technological innovation and the legal, regulatory, economic and social aspects; underscoring the influence of the telephone on the evolution of language, customs and means of expression, and finally co-ordinating and enhancing other initiatives not directly sponsored by the Committee. This book "Il telefono & dintorni" brings together a selection of the events, contributions and 'images' selected from among the numerous initiatives organised by the Meucci Committee over its three years of activity.